Encyclopedia of religious ethics - Schweiker, William (Wiley-Blackwell, 2022)
"The Encyclopedia of Religious Ethics introduces readers to basic issues in moral inquiry, a selection of moral traditions, and surveys a range of moral issues. Each of the three volumes covers one of these three elements of religious ethics, with Volume I focusing on moral inquiry. What distinguishes "religious" ethics from other approaches to ethics is, first and foremost, its connection to the religions. While there is much debate in modern scholarship about the precise meaning of the term "religion" there is at least a widely shared conviction that there are such things as religions, by which is meant social groups and traditions of thought and practice that are in one way or another about the deepest human questions and the ultimate goal(s) of human life, including but not limited to reverence for a divine being or beings. Thought about or practice in relation to what is held to be ultimately real and important seems to be a longstanding feature of human life across historical periods, geography, and cultural traditions"--